IMPACT OF MOTOR FITNESS VARIABLES AND PLAYING ABILITY AMONG BASKETBALL MEN PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the study was to find out the relationship between selected motor fitness variables and playing ability among Basketball players. To achieve the purpose of this study the investigator selected hundred college men Basketball players from the affiliated colleges of Tamil Nadu Physical Education and Sports University at randomly and their age ranged between 17 to 25 years. The following Motor Fitness variables will be selected to this study: muscular strength, muscular endurance, cardio-vascular endurance, flexibility, body mass index, power, speed, agility, balance and reaction time. Obtained data were analyzed with the Pearson product moment correlation. Power with muscular strength, muscular endurance, cardio vascular endurance, flexibility, body mass index, agility, balance and reaction time. Speed and muscular strength, muscular endurance, cardio -vascular endurance, flexibility, agility, balance, and reaction time. Agility flexibility, body mass index, power, speed and reaction time. balance with muscular strength, muscular endurance, cardio -vascular endurance, flexibility, power, speed, and reaction time. reaction time with cardio -vascular endurance, flexibility, power, speed, agility, and balance.